The growth of zinc phthalocyanine thin films by pulsed laser deposition. Issue 1 (14th January 2016) - Novotný, Michal; Šebera, Jakub; Bensalah-Ledoux, Amina; Guy, Stephan; Bulíř, Jiří; Fitl, Přemysl; Vlček, Jan; Zákutná, Dominika; Marešová, Eva; Hubík, Pavel; Kratochvílová, Irena; Vrňata, Martin; et al.
Abstract: Abstract : Zinc phthalocyanine (ZnPc) thin films were prepared by pulsed laser deposition (PLD) using KrF laser (λ = 248 nm, τ = 5 ns). The effect of laser fluence (in the region from 10 to 100 mJ/cm 2 ) and repetition rate of 50 and 200 Hz to the film growth and its properties was investigated. The growth of ZnPc thin film was in situ monitored using transmission measurement in ultraviolet-visible spectral range. The optical properties in conjunction with density functional theory/time-dependent density functional theory calculations suggested the growth of the film in β-phase. X-ray diffraction also revealed crystalline character of the film. The electrical properties analyzed by van der Pauw method exhibited resistivity ρ ≈ 10 8 –10 10 Ω cm. Fourier transform infrared spectroscopy analyses revealed low deterioration of PLD deposited ZnPc films. We demonstrate that, by finely tuning the deposition conditions, PLD is a successful technique for fabrication of ZnPc thin films.